2012
DOI: 10.1242/jcs.104059
|View full text |Cite
|
Sign up to set email alerts
|

The centriolar satellite protein Cep131 is important for genome stability.

Abstract: SummaryThe centrosome acts as a centre for microtubule organisation and plays crucial roles in cell polarity, migration, growth and division. Cep131 has recently been described as a basal body component essential for cilium formation, but its function in non-ciliogenic cells is unknown. We identified human Cep131 (also known as AZI1) in a screen for regulators of genome stability. We show that centrosomal localisation of Cep131 is cell-cycle-regulated and requires both an intact microtubule network and a funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
101
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(124 citation statements)
references
References 45 publications
22
101
1
Order By: Relevance
“…In line with this notion, PCM1 particles still localize around the centrosome after the depletion of several satellite components (Staples et al ., 2012; Lee and Stearns, 2013). The depletion of certain other components alternatively causes the distribution pattern of PCM1 to become more dispersed (Lopes et al ., 2011; Kim and Rhee, 2012).…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…In line with this notion, PCM1 particles still localize around the centrosome after the depletion of several satellite components (Staples et al ., 2012; Lee and Stearns, 2013). The depletion of certain other components alternatively causes the distribution pattern of PCM1 to become more dispersed (Lopes et al ., 2011; Kim and Rhee, 2012).…”
Section: Introductionmentioning
confidence: 56%
“…Recent studies show that in addition to hMsd1/SSX2IP, multiple molecules and pathways are involved in the suppression of supernumerary centriole formation. These include Cep76 (Tsang et al ., 2009), LGALS3BP (Fogeron et al ., 2013), Cep131/Azi1 (Staples et al ., 2012), and CCDC14 (Firat-Karalar et al ., 2014). Of interest, the depletion of these molecules has a variety of effects in nontransformed and cancer cells, often varying within specific lines (Staples et al ., 2012; Fogeron et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently carried out a genome-wide small interfering RNA (siRNA) screen in HCT116 colorectal carcinoma-derived cells to identify previously uncharacterized regulators of genome stability, using phosphorylation of the histone variant H2AX on Ser139 (γH2AX) as a marker of increased DNA damage (Staples et al., 2012, Staples et al., 2014). From this screen, we identified C5orf45, which yielded a relatively high Z score of 1.7.…”
Section: Resultsmentioning
confidence: 99%
“…For example, deficiency of centrosomal proteins, such as pericentrin (PCNT), CEP131, CEP152, and CEP164, causes DDR defects. [12][13][14][15] On the other hand, deficiency of certain DDR proteins, including BRCA1, induces centrosome amplification. 16,17 Further supporting this connection, it has long been observed that a variety of genotoxic stress can induce pronounced centrosome amplification (DNA damage induced centrosome amplification, or DDICA).…”
Section: Introductionmentioning
confidence: 99%